‘Dragonisation’ revisited: A progressive criminal justice policy in Wales? - Evans, Jonathan (Criminology & criminal justice, 2022)
The concept of ‘dragonisation’ was the first authoritative attempt to engage with criminal justice policy in post-devolution Wales. Its central claim, that devolution created the space and conditions for progressive justice policy to flourish in Wales while remaining part of the unitary England and Wales jurisdiction, remains largely unchallenged more than a decade since it first entered Welsh criminological vocabulary. By reviewing policy developments and drawing upon empirical research, this article revisits dragonisation to assess the extent to which Welsh policy has continued to diverge from England since the formative years of devolution. The arguments presented here contribute to emerging discussions over the future of criminal justice policy in Wales and form part of a wider criminological research agenda aimed at producing fine-grained territorial analyses of criminal justice practices, including differences within the same jurisdiction.